New critical spaces in transitional justice : gender, art, and memory - Kurze, Arnaud; Lamont, Christopher K. (Bloomington, Indiana : Indiana University Press, 2019)
Gathering work from contributors in international law, political science, sociology, and history, New Critical Spaces in Transitional Justice explains current trends in responses to post-conflict and post-authoritarian nations and offers original empirical research to help define the field for the future.
10. Dignity for the Defeated: Recognizing the "Other" in Post-Yugoslav Commemorative PracticesConclusion: Practicing Critical Transitional Justice and the Road Ahead; Bibliography; Index; About the Editors
Includes bibliographical references and index.
Online resource; title from PDF title page (EBSCO, viewed February 1, 2019).
eBooks on EBSCOhost
Keywords: Transitional justice; Human rights; Identity politics; Justice transitionnelle; Droits de l'homme (Droit international); Politique identitaire; POLITICAL SCIENCE -- Political Freedom & Security -- Civil Rights; POLITICAL SCIENCE -- Political Freedom & Security -- Human Rights; Human rights; Identity politics; Transitional justice; Transitional Justice